ANALISIS TEKNIK SCREENLIFE/SCREEN RECORD: SEBUAH STUDI KASUS TENTANG PENGARUHNYA PADA PENCERITAAN FILM - Fikri, Muhammad Ihsanul (Institut Seni Indonesia Padangpanjang, 2024)
creenlife/screen record, a filmmaking technique that utilizes screen recordings of electronic devices, has garnered significant attention from filmmakers and audiences in recent years. This research employs a qualitative approach with a case study method to analyze screenlife/screen record, focusing on its advantages and disadvantages, its influence on film storytelling, and the challenges faced by filmmakers. The research findings indicate that screenlife/screen record offers realism, audience immersion, and low production costs. However, this technique also presents limitations in story scope, the potential for audience boredom, and the requirement for specialized technical skills. Screenlife/screen record enables filmmakers to explore contemporary themes, deliver immersive and personal narratives, and introduce new perspectives in film storytelling. This research holds implications for filmmakers, academics, and the film industry as a whole. Filmmakers can utilize the research findings to understand the pros and cons of screenlife/screen record and to address the challenges encountered in filmmaking using this technique. Academics can contribute to the development of knowledge about screenlife/screen record and its role in film storytelling. The film industry can recognize screenlife/screen record as a potential genre to capture audience interest and drive innovation in filmmaking.